KEPUTUSAN PEMBELIAN PRODUK MIXUE ICE CREAM & TEA PADA GENERASI Z : KETERLIBATAN TAQWA SEBAGAI PEMODERASI - Amaliyah, Laili; Pratama, Abdul Aziz Nugraha (Economic and Science Faculty of Islamic State University, 2024)
This study aims to answer the influence of word of mouth, viral marketing and online customer reviews on purchasing decisions for Mixue Ice Cream products in generation z with taqwa as a moderating variable. This research was conducted in the city of Salatiga. Data collection was carried out by distributing questionnaires using a Likert scale (1-5) to 100 mixue consumers who were respondents in this study. The data analysis technique used in this study is the MRA (Moderated Regression Analysis) method. The results of testing the hypothesis show that word of mouth has a positive effect on purchasing decisions. Viral marketing has no effect on purchasing decisions. Online customer reviews have a positive influence on purchasing decisions. Taqwa is able to moderate the influence of word of mouth on purchasing decisions. Taqwa is able to moderate the effect of viral marketing on purchasing decisions. Taqwa is able to moderate the influence of online customer reviews on purchasing decisions.